2017
DOI: 10.1038/s41598-017-05282-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Retinal Inner Nuclear Layer Thickness and Severity of Visual Field Loss in Glaucoma

Abstract: Glaucoma is a disease characterized by pathologic changes in inner retinal layers, which are comprised of retinal ganglion cells (RGCs). As retinal ganglion cells (RGCs) cross over other retinal neurons that are connected by synapses, it is meaningful to investigate the outer retinal changes in glaucoma. We evaluated the association between thicknesses of segmented retinal layers in macular region and severity of visual field loss in open-angle glaucoma (OAG). This study involved 103 glaucomatous eyes. Retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
2
18
5
Order By: Relevance
“…The GCL and IPL thickness is known to be affected by glaucoma and vision loss to be decreased. 22 The results of current study did not show any of the reported symptoms and the inflammation caused by corneal alkali burn was alleviated by hyaluronic acid and Solcoseryl treatments.…”
Section: Discussioncontrasting
confidence: 66%
“…The GCL and IPL thickness is known to be affected by glaucoma and vision loss to be decreased. 22 The results of current study did not show any of the reported symptoms and the inflammation caused by corneal alkali burn was alleviated by hyaluronic acid and Solcoseryl treatments.…”
Section: Discussioncontrasting
confidence: 66%
“…4G ) was also found in the outer plexiform layer (OPL). In a summarized retinal layers overview; a) RPE cells are involved in the regeneration and repair of photoreceptor cells 40 ; b) The normal ONL contains rod and cone photoreceptor nuclei throughout the retina 41 ; c) INL consist of bipolar cells, which are directly synapsed to retinal ganglion cells and Müller glial cells 42 ; d) and OPL has a certain degree of integration of the visual message takes place at the first synapse in the retina 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 36 reported that INL thickness is negatively correlated with the severity of glaucoma. Although the scatterplots showed a significant correlation between N1–P1 amplitude and mINOPL thickness ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%